ANALISIS PENGARUH SELFIE PADA PROSES PENGAMBILAN KEPUTUSAN PELANGGAN BERBASIS AISAS - Faisal Sa'ban; Salamatun Asakdiyah; Zunan Setiawan; Fitroh Adhilla; Agus Siswanto (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study examines and analyzes the effect of the selfie promotion method on the customer's decision-making process using the AISAS model. Data were assessed and analyzed using PLS-SEM modeling. The results show that the AISAS model with selfie promotion produces better in-sample predictions (model selection criteria). This study is important to understand the effect of advertising-supported selfie promotion on decision-making processes and provide insight into how companies can leverage advances in communication technology to drive selfie-driven behavior promoting innovative and competitive products. Assessment of the effect of selfie promotional advertisements on the decision-making process using PLS-SEM and model selection criteria for articulating the relevance of selfies as a promotional tool.